Medical Journal of Indonesia Vol.23 Issue 4 November 2014 - Redaksi (FK Universitas Indonesia, 2014)
-Hibiscus Sabdariffa in Physical Exercise -Hibiscus Sabdariffa Prevents Insulin Resistance -p53, Topoisomerase-IIa and Basal-like Breast Cancer -Cytotoxic Effect of y-Sitosterol from Kejibeling -Quality of Stored Blood in Thalassemia Donor -NF-kB, TNFa, and COX-2 in Preterm Labor -POUR Incidence after POP Surgery in RSCM -Lymphocyte Chromosome Breakage in Low Benzene Exposure -Primary Rectal Melanoma -Pulmonary Hpertension in Young Woman -Antioxidant Properties of Flavonoids